Base Changeable Sets and Mathematical Simulation of the Evolution of Systems - Hrushka, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We introduce the notion of base changeable sets and study the principal properties of these sets. Base changeable sets are required for the construction of the general theory of changeable sets. The problem studied in our paper is closely connected with the famous sixth Hilbert problem.